Producción y calidad de agua en el manejo de juveniles de Arapaima gigas en tanques y en un sistema acuapónico en la región Loreto - Berger Peña, Gabriel Junior (2025)
The present study was conducted at the facilities of the NGO Amazon Research Center for Ornamental Fishes (ARCOF), located at A. H. 31 de mayo, km 0.6 of the Zungarococha Highway, San Juan Bautista, Loreto, Peru, during the month of September 2022. The objective was to evaluate the production and quality of water in the management of juvenile “paiche” Arapaima gigas, in tanks and in an aquaponic system. A completely randomized design (CRD) was established and juvenile A. gigas “paiche” and lettuce seedlings were purchased from local suppliers. The fish were transported to the research facilities where tanks (T1) and an aquaponic system (T2) were used for the experimental units. Sixty specimens were used and fed twice a day with balanced feed for 90 days. physical and chemical parameters of the water were evaluated weekly, including temperature, conductivity, TDS and pH. The average initial weight of paiche juveniles was 12 g and average size was 12.5 cm. It was determined that A. gigas juveniles in the aquaponic system show a significant increase in weight (188.93 g vs. 178.19 g in the tanks); the length is significantly greater in the aquaponic system (45.86 cm vs. 37.46 cm in the tanks). Regarding the use of the aquaponic system, A. gigas presented a significant increase in daily weight (1.94 g/day vs. 1.81 g/day in the tanks). In addition, the aquaponic system has a better ICAA (T1: 1.90 vs. T2: 2.07) and a more favorable K (T1: 0.34% vs. T2: 0.20%), being in all comparisons p<0.05. In terms of cost per kilogram of fish, the aquaponic system is more economical (S/. 14.82 vs. S/. 16.15 in the tanks), with a similar energy consumption of s/. 86.83 during 90 days. In conclusion, the aquaponic system generates additional income through lettuce culture, offering better conditions for the growth of juvenile A. gigas compared to tanks, with a significant increase in weight and length, as well as an improvement in feed conversion parameters.